Improving irrigation in Asia sustainable performance of an innovative intervention in Nepal - Ostrom, Elinor; Edward Elgar Publishing (Cheltenham, U.K. : Edward Elgar, 2011)
Improving Irrigation in Asia is based on a longitudinal study over two decades on innovative intervention for sustained performance of irrigation systems. The work identifies key factors that can help explain the performance of interventions, and explicates lessons for resource management and the management of development assistance.
1. The challenge of achieving successful development interventions -- 2. Effects of different modes of assistance on the performance of farmer-managed irrigation systems in Nepal -- 3. Processes and procedures of an innovative development intervention initiated in 1985 in the Middle Hills of Nepal -- 4. Evaluating an innovative development intervention a decade and a half later -- 5. Post-intervention dynamics in 2008 : focusing on two success and two failure cases -- 6. Synthesis and conclusion.
Includes bibliographical references and index.
Keywords: Irrigation -- Nepal; Sustainable agriculture -- Nepal; Electronic books